Spontaneous preterm delivery in primiparous women at low risk in Denmark: population based study. Issue 7547 (23rd February 2006) - Langhoff-Roos, Jens; Kesmodel, Ulrik; Jacobsson, Bo; Rasmussen, Steen; Vogel, Ida
Abstract: Objectives To analyse trends in preterm delivery and the factors contributing to preterm delivery in Denmark. To construct a standard population at low risk (white European, 20-40 years of age, with a singleton spontaneous pregnancy) and describe the changes in this population so that time trends can be compared internationally. Design Population based study. Participants 99.8% of all deliveries in Denmark, 1995-2004. Main outcome measures Proportion of babies born at less than 37 weeks' completed gestation for each year in the overall population and in a standard population at low risk. Results Overall, the proportion of preterm deliveries increased by 22% from 1995 to 2004. During the same period, known risk factors for preterm delivery such as in vitro fertilisation, multiple pregnancies, and elective deliveries also increased, and logistic regression analyses showed that these factors were associated with an increased risk of preterm delivery. Spontaneous preterm deliveries in primiparous women at low risk rose 51% (from 3.8% to 5.7%) during this time compared with 20% (2.7% to 3.2%) in multiparous women at low risk. Conclusions The overall proportion of preterm deliveries increased significantly from 1995 to 2004 and primiparity and multiple birth were the most important contributing factors. The rise in spontaneous preterm deliveries in the standard population of primiparous women at low risk was greater than in the total population.